2022
DOI: 10.4269/ajtmh.21-1309
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Progress Accelerating Malaria Control in Mali: Evidence from the West Africa International Center of Excellence for Malaria Research

Abstract: ABSTRACT. This article highlights over a decade of signature achievements by the West Africa International Centers for Excellence in Malaria Research (WA-ICEMR) and its partners toward guiding malaria prevention and control strategies. Since 2010, the WA-ICEMR has performed longitudinal studies to monitor and assess malaria control interventions with respect to space-time patterns, vector transmission indicators, and drug resistance markers. These activities were facilitated and supported by the Mali National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Through November 2022, a total of 4556 children were enrolled during the pilot phase (2019-2020) in 9 villages across the Koulikoro Health District. In 2022, preliminary findings have been presented at the American Society of Tropical Medicine Conference [ 16 ] and published in the American Journal of Tropical Medicine and Hygiene [ 17 ]. SP-AQ and DHA-PQ were highly effective in reducing P falciparum malaria in children 5-9 years in Koulikoro, Mali, at both the pilot and district-wide study phases.…”
Section: Resultsmentioning
confidence: 99%
“…Through November 2022, a total of 4556 children were enrolled during the pilot phase (2019-2020) in 9 villages across the Koulikoro Health District. In 2022, preliminary findings have been presented at the American Society of Tropical Medicine Conference [ 16 ] and published in the American Journal of Tropical Medicine and Hygiene [ 17 ]. SP-AQ and DHA-PQ were highly effective in reducing P falciparum malaria in children 5-9 years in Koulikoro, Mali, at both the pilot and district-wide study phases.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that WHO updated its recommendations on SMC in the WHO Guidelines for Malaria in June 2022, which is more flexible and different from the original 2021 version in a couple of significant ways: Areas outside the Sahel with highly seasonal malaria transmission could also benefit from SMC; SMC can be given without defining the specific number of cycles; SMC can be extended to children over six years old. The move by WHO has enabled National malaria programs (NMPs) in local countries to tailor their strategies to the settings and increase the impact of SMC when applied together with LLINs and the malaria vaccine [ 51 , 60 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…As SMC and PMC are rolled out over larger areas, monitoring for antimalarial resistance will be important. Recent studies disagree on SMC's effects on resistance, with some showing an increase in molecular resistance markers and others showing that resistance markers remained rare [22 ▪▪ ,25–27]. Also, in an area with previously documented high levels of molecular resistance markers, SMC with SP+AQ remained highly effective, so the clinical relevance of molecular resistance markers is not always clear [14 ▪ ].…”
Section: Malaria Chemopreventionmentioning
confidence: 98%
“…Although the WHO recommends SP+AQ specifically for SMC because of long-term studies that show benefit without serious adverse events, some groups have explored therapeutic alternatives to SP+AQ. A study done in Mali indicated that dihydroartemisinin-piperaquine (DHA+PQ) is potentially more efficacious than SP+AQ against clinical malaria in children 3 months to 5 years of age [22 ▪▪ ]. Another trial done in Mali reported similar performance of DHA+PQ and SP+AQ, and that DHA+PQ was better tolerated, with lower rates of abdominal pain, headache, and vomiting [23 ▪ ].…”
Section: Malaria Chemopreventionmentioning
confidence: 99%